A Deconstructionist Reading of The Waste Land (المجلة الدولية للبحوث العلمية, 2024)
The Waste Land offers no hope for redemption or salvation. The poem's ending is ambiguous and inconclusive, and it is unclear whether the Fisher King, who is a symbol of fertility and renewal, is able to heal the wasteland. The meaning of the Waste Land is up to the individual reader to decide. The poem's deconstructionist elements allow it to be interpreted in many different ways, and each reader will come away with their own unique understanding of the poem.